Pesticides - Matthews, G. A (Wiley Blackwell, 2016)
Includes bibliographical references and index; Pesticides and agricultural development -- Approval of pesticides -- Application of pesticides -- Operator exposure -- Spray drift, bystander, resident and worker exposure -- Environmental aspects of spray drift -- Residues in food -- The future of pesticides